PENGARUH KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (STUDI KASUS PADA DON’S WARNET) - Asep Dony Suhendra; Ratih Dwi Asworowati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Abstract This research aims to identify and examine the factors that may affect the customer's satisfaction and loyalty in Don's Warnet Cikarang. With a sample size of 200 people, the research carried out on the visitors who have used the services of Don's Warnet, and conducted by purposive sampling technique. The results show that customer satisfaction is positively and significantly influenced by the quality of service and location factors. As for the only customer loyalty is positively and significantly influenced by customer satisfaction factors. The moderating variable frequency of visits and customer's place of residence does not give significant results on satisfaction and customer loyalty. Thus , it can be concluded that in order to get satisfaction and customer loyalty , besides place the business location that is close to the customer's environment, Don 's Warnet should further improve the quality of services , especially in the field of reliability of internet access , responsiveness operators , security environment and a sense of empathy towards the customer . So the satisfaction perceived by customers, is expected to make a loyal customer to the products / services used. Abstract This research aims to identify and examine the factors that may affect the customer's satisfaction and loyalty in Don's Warnet Cikarang. With a sample size of 200 people, the research carried out on the visitors who have used the services of Don's Warnet, and conducted by purposive sampling technique. The results show that customer satisfaction is positively and significantly influenced by the quality of service and location factors. As for the only customer loyalty is positively and significantly influenced by customer satisfaction factors. The moderating variable frequency of visits and customer's place of residence does not give significant results on satisfaction and customer loyalty. Thus , it can be concluded that in order to get satisfaction and customer loyalty , besides place the business location that is close to the customer's environment, Don 's Warnet should further improve the quality of services , especially in the field of reliability of internet access , responsiveness operators , security environment and a sense of empathy towards the customer . So the satisfaction perceived by customers, is expected to make a loyal customer to the products / services used.